A case-based reasoning system for classifying Malay traditional herbs / Ismaily Johari - Ismaily , Johari (2003)
The purpose of this project is to develop a system using case-based reasoning to classify the various types of Malay Traditional herbs. The task of classifying Malay Traditional herbs had always been done by botanist. Malay Traditional herbs practitioner, herbalists and people interested on the herbs. The classification were usually done by identifying the physical attributes of the herbs, based on the features of its leaf, root, flower, fruit and stem. Each of them owns its own unique physical features making the process of classifying essential to determine the type of the herbs. This project focuses on the methods of indexing the herbs into a case and it into the case library using the case based reasoning techniques. Also being emphasized in this project is the method of matching and retrieval of the cases in order to retrieve the best solution from the case library. Besides that, the other purpose of this project is to evaluate the effectiveness of implementing case based reasoning to classify Malay Traditional herbs.